1995
DOI: 10.1016/0029-7844(95)00237-l
|View full text |Cite
|
Sign up to set email alerts
|

The Fertility of Women After Cervical Laser Surgery

Abstract: Cervical laser surgery does not appear to impair a woman's ability to conceive or carry a pregnancy to term. There is no difference in the effect on fertility between laser vaporization and laser excisional cone biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…Our finding that ablative treatment is associated with an elevated risk of pregnancy loss is in conflict with the one other examination of this association (RR = 0.65, 95% CI 0.39–1.09) and requires confirmation in other studies [41]. Similar to our study, a recent meta-analysis of nine studies [42] reported no overall association between excisional treatment and miscarriage.…”
Section: Discussioncontrasting
confidence: 54%
“…Our finding that ablative treatment is associated with an elevated risk of pregnancy loss is in conflict with the one other examination of this association (RR = 0.65, 95% CI 0.39–1.09) and requires confirmation in other studies [41]. Similar to our study, a recent meta-analysis of nine studies [42] reported no overall association between excisional treatment and miscarriage.…”
Section: Discussioncontrasting
confidence: 54%
“…Although large registry-based studies of treatment with mixed modes of conization provide some evidence that cervical treatment is associated with preterm birth, 3,4 studies of cold-knife conization, [5][6][7][8][9][10] laser conization, [11][12][13][14][15] or LEEP [16][17][18][19][20][21] alone have been limited and inconclusive. Most studies were small and lacked the statistical power necessary to detect a doubling of risk.…”
mentioning
confidence: 99%
“…Most studies were small and lacked the statistical power necessary to detect a doubling of risk. [6][7][8][12][13][14][15][16][17]19,21 Only a handful of studies controlled for potentially important confounding by smoking and socioeconomic status, 3,14 analyzed treatment by depth of tissue excised, 11,12,14,22,23 or evaluated risk of preterm delivery by its specific subtypes (ie, medical induction, premature rupture of membranes before 37 weeks' gesta-tion [pPROM], and spontaneous preterm labor), 5,19,24,25 which are likely to be etiologically distinct. 26 It is plausible that cervical excisional or ablative treatments might affect the risk of preterm delivery by reducing the mechanical support provided by a short-ened cervix, by impairing local immunological defense mechanisms by destruction of glandular epithelia, or by altering cervicovaginal bacterial flora.…”
mentioning
confidence: 99%
“…Long-term complications are fewer after ablative treatments than after excisional procedures. Ablative treatments are not associated with adverse effects on pregnancy outcomes such as miscarriage, preterm labor or with infertility and other adverse events such as cervical stenosis [4,5,10,11]. Women should receive instructions on self-care, symptoms to expect and on follow-up care after completion of ablative treatment.…”
Section: Ablative Treatmentmentioning
confidence: 99%